THE ROLE OF TRUST IN MEDIATING PERCEIVED EASE OF USE, PERCEIVED RISK AND E-WOM ON PURCHASE INTENTION - Nuri Aslami; Ari Apriani; Cristina Catur Widayati; Rizky Vita Losi (Fakultas Bisnis dan Ilmu Sosial Universitas Dian Nusantara, 2022)
This study aims to determine the direct effect of perceived ease of use, perceived risk and E-WOM on trust and purchase intention, and also to determine the indirect effect of perceived ease of use, perceived risk and E-WOM on purchase intention which is mediated by trust. The population in this study were all shopee users in West Jakarta with a sample of 260 respondents. The method used in this research was quantitative analysis with SEM analysis assisted with SmartPLS 3.0 tool. The results of this study indicated that perceived ease of use had no significant effect on trust, perceived risk had no significant effect on trust, E-WOM had a positive and significant effect on trust, perceived ease of use had a positive and significant effect on purchase intention, perceived risk did not have significant effect on purchase intention, E-WOM had a positive and significant effect on purchase intention, trust had a positive and significant effect on purchase intention, thus trust could not mediate the effect of perceived ease of use on purchase intention, trust could not mediate the effect of perceived risk on purchase intention, and trust could mediate the effect of E-WOM on purchase intention.